UBUNGAN PERSONAL HYGIENE DENGAN KONTAMINASI TELUR SOIL TRANSMITTED HELMINTHS PADA KUKU DAN TANGAN SISWA SDN 07 MEMPAWAH HILIR KABUPATEN PONTIANAK - ., Desti Eryani (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background: Soil Transmitted Helminths infection is one of the healthproblems with high prevalence in tropic and subtropic countries especiallyIndonesia. Children from primary schooling age have the higest prevalenceof infection, because awareness in keeping hygiene is still low. Objective :this study aims to determine the relationship of personal hygiene with SoilTransmitted Helminths contamination of STH egg on student’s nail and handin SDN 07 Mempawah Hilir, Kabupaten Pontianak. Method: The study wasa analitic observational study with cross sectional design. The study wasconducted in SDN 07 Mempawah Hilir, Kabupaten Pontianak from March2014 until September 2014. Fourty four students grade 1 to 6 wereparticipated in this study. The subjects were chosen by using stratifiedrandom sampling method. Questionnaire was used to evaluate the level ofpersonal hygiene and laboratory test  used stoll method modification todetermined Soil Transmitted Helminths contamination in nail and handcaress of  student. Result. There were 29,5% students infested by STH  intheir hand and their nail, among them were 15,8 % male students and 11,7 %female students. STH contamination most occurred is 11,34% in 6-8  yearsold students. STH species that caused the contamination were Ascarislumbricoides (61,50%), Trichuris trichiura (15,4%), hookworm (23,1%).Fisher’s exact test show p=0,001(p<0,005) with coefesien contingency 0,484.It’s mean personal hygiene has a significant relationship to the STH eggcontamination on student’s nail and hand in SDN 07 Mempawah Hilir,Kabupaten Pontianak. Conclusion: There has correlation between pesonalhygiene with Soil Transmitted Helminths contamination on student’s nail andhand in SDN 07 Mempawah Hilir, Kabupaten Pontianak.Key words: Soil transmitted helminths, Personal Hygiene, nail and hand’scontaminationNote:1)Medical School, Faculty of Medicine, Tanjungpura University, WestKalimantan.email: eryanidesti@yahoo.co.id2)Departement of of Community Medicine, Faculty of Medicine,Tanjungpura University, West   Kalimantan.3)Departement of Parasitology, Faculty of Medicine, TanjungpuraUniversity, West   Kalimantan.